Twist : a novel [large type] - McCann, Colum, 1965- (Random House Large Print, 2025)
"Anthony Fennell, an Irish journalist and playwright, is assigned to cover the underwater cables that carry the world's information. The sum of human existence--words, images, transactions, memes, voices, viruses--travels through the tiny fiber-optic tubes. But sometimes the tubes break, at an unfathomable depth. Fennell's journey brings him to the west coast of Africa, where he uncovers a story about the raw human labor behind the dazzling veneer of the technological world. He meets a fellow Irishman, John Conway, the chief of mission on a cable repair ship. The mysterious Conway is a skilled engineer and a freediver capable of reaching extraordinary depths. He is also in love with a South African actress, Zanele, who must leave to go on her own literary adventure to London. When the ship is sent up the coast to repair a series of major underwater breaks, both men learn that the very cables they seek to fix carry the news that may cause their lives to unravel."--